Human Rights, Violence and the Camp Paradigm: A Critical Reception Built from the Arendtian Work - Mallmann Marcht, Laura (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The present critical review, through the hypothetical-deductive method, aims to analyze some of the main works of the philosopher Hannah Arendt - The human condition, Eichmann in Jerusalem and Origins of totalitarianism - from its main commentators, as well as the issues that permeate human rights, violence and the rural paradigm. The Arendtian work, as it is commonly known, is of fundamental importance for researchers in the area of ​​philosophy, law and similar sciences, since it is only through human rights - or as this author refers, from the “right to have rights”- that it is possible to avoid the repetition of the horrors of totalitarianism - and that is why this brief search is justified.
Keywords: Human rights; Hannah Arendt; Totalitarianism; Violence